Genetic susceptibility of MMP3 (rs3025058) variant allele in male football players with multiple ACL surgeries: a PCR-RFLP analysis - Alpay Bülbül; Çağatay Dereceli; Meriç Eraslan; Nihan Bozkurt; Kübra Şahin; Murat Eliöz; Dila Şeyda Taşdemir; Yunus Emre Güler (Journal of Men's Health)
This study aimed to investigate the genetic susceptibility of the Matriks Metalloproteinaz-3 (MMP3) (rs3025058) gene variant allele and genotype distribution in male football players who actively participate in professional leagues and have undergone a minimum of two anterior cruciate ligament (ACL) surgeries. The study comprised 44 male football players who had undergone a minimum of two ACL surgeries and 61 male football players who had not undergone any ACL surgery. Participants’ blood samples were collected and DNA was extracted. Allele types were determined by analyzing the MMP3 (rs3025058) variant gene polymorphism using the restriction fragment length polymorphism (PCR-RFLP) method with appropriate primers and restriction enzymes. The results revealed no statistical significant differences in genotype distribution for 6A/6A, 5A/6A and 5A/5A (p = 0.736) or in 6A-allele frequency distribution between the control (CON) and ACL groups (Odds Ratio (OR) = 1.119, 95% Confidence Interval (CI): 0.637–1.965; p = 0.318). The analysis of both dominant (6A/6A vs. 5A/6A + 5A/5A) and recessive (6A/6A + 5A/6A vs. 5A/5A) models for the inheritance of the minor allele did not yield statistically significant difference, with odds ratios (OR) of 0.647 (95% CI: 0.283–1.478; p = 0.408) and 1.472 (95% CI: 0.506–4.281; p = 0.584), respectively. This study investigated the impact of MMP3 gene polymorphisms in ACL injuries, uncovering an intricate interplay between genetic and environmental factors that contribute to injury susceptibility. While some studies suggest potential links between MMP3 variants and ACL risks, the available information is inconclusive and necessitates additional confirmation in other demographics. Continued research is crucial to develop effective, personalized injury prevention strategies based on robust genetic markers.